Conservation policies of the National Parks Administration (Argentina) through protected areas, period 2000-2022 - Caruso, Sergio-Adrian (2024)
In Argentina, from the beginning of the 21st century onwards, it has been detected that the conservation policies deployed by the National Parks Administration have been characterized by creating numerous protected areas and extending existing ones. During these years two concurrent processes also took place. One of them, related to the adoption and consolidation of neo-extractivism as a productive model whose modalities plundered the ecosystem functions of ecoregions throughout the entire national territory. The remainder was associated with the commitments assumed by the country before the Convention on Biological Diversity through the Aichi Goals. Therefore, it is hypothesized that both processes conditioned the conservation policies of said organism during the period 2000-2022. It is concluded that these policies were reactive and compensatory when seeking to protect the relics of the ecoregions not eradicated by neo-extractivism. At the same time, they tried to comply with the international commitments assumed.